THE INFLUENCE OF ACCOUNTING LITERACY AND TAX LITERACY ON INTEREST IN BECOMING A TAX CONSULTANT WITH A MODERATED GROWTH MINDSET - Fredicia Putri, Cindy; Rodiah, Siti; Mustika Putri, Annie (LP2M IBK Nitro, 2025)
This study was conducted to examine the influence of accounting literacy, tax literacy, and growth mindset on students' interest in becoming tax consultants, as well as the role of growth mindset in moderating this relationship. The study population included all students of the Accounting Study Program at the University of Muhammadiyah Riau, with a sample of 151 respondents selected through purposive sampling. Data were obtained through questionnaires. The results showed that accounting literacy did not significantly influence students' interest in becoming tax consultants. Tax literacy was proven to have a positive and significant effect on interest in becoming tax consultants. Growth mindset also had a significant positive effect on students' interest. However, growth mindset did not act as a moderating variable in the relationship between accounting literacy and tax literacy. The conclusion of this study confirms that tax understanding and growth mindset are more dominant in driving students' interest in choosing the profession of tax consultant than accounting literacy factors.